2020
DOI: 10.1186/s13643-020-01504-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening for sickle cell disease in newborns: a systematic review

Abstract: Background Sickle cell disease (SCD) is an inherited autosomal recessive disorder caused by the replacement of normal haemoglobin (HbA) by mutant Hb (sickle Hb, HbS). The sickle-shaped red blood cells lead to haemolysis and vaso-occlusion. Especially in the first years of life, patients with SCD are at high risk of life-threatening complications. SCD prevalence shows large regional variations; the disease predominantly occurs in sub-Saharan Africa. We aimed to systematically assess the evidence on the benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…This investigation discovered changes in hematological parameters, primarily among SCA patients, due to Hb abnormalities, recurrent infection-induced hemolytic processes, and coagulopathy. 11 MCV and RDW were both significantly increased in SCA patients compared with the national norm. MCV was higher in the majority of patients with the HbSS and HbAS genotypes, which could be attributable to enhanced hemolysis.…”
Section: Discussionmentioning
confidence: 75%
“…This investigation discovered changes in hematological parameters, primarily among SCA patients, due to Hb abnormalities, recurrent infection-induced hemolytic processes, and coagulopathy. 11 MCV and RDW were both significantly increased in SCA patients compared with the national norm. MCV was higher in the majority of patients with the HbSS and HbAS genotypes, which could be attributable to enhanced hemolysis.…”
Section: Discussionmentioning
confidence: 75%
“…A study in the United States identified a reduction in the mortality rate of children and adolescents from 1983 to 2002, more pronounced among children under three years of age (68% reduction, 95%CI: 58; 75) and progressively lower in children aged 4-14 years 22 . Although the authors had attributed this reduction to the universal access to the newborn screening programs for hemoglobinopathies and the prophylactic penicillin, only one retrospective cohort study conducted in Jamaica provided robust evidence on the performance of newborn screening, followed by measures to prevent infection and orient parents about the disease 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Newborn screening (NBS) coupled with comprehensive care is proven to reduce mortality and morbidity caused by SCD (18)(19)(20). Unfortunately, most African countries have not been able to establish national NBS programs due to various reasons including cost and limited human and logistical resources (21).…”
Section: Discussionmentioning
confidence: 99%